Investigation of tensile properties and microstructural evolution of Al–Mg–Si alloy produced through the multi-axial forging at −147 C and room temperature - Kumar N. (My University, 2025)
In current investigation, effect of Multi-axial forging (MAF) processing temperature on microstructural evolution and mechanical properties of Al–Mg–Si alloy was investigated by performing MAF at (i) −147 °C (CT-MAF) and (ii) room temperature (RT-MAF). The electron Back scattered diffraction (EBSD) and transmission electron microscopy (TEM) were used for exploring the microstructural evolved. It was observed that MAF at −147 °C helped in accumulation of large amount of dislocations as confirmed from the TEM. The recovered, recrystallized, sub-grain and deformed grains were separated with the help of EBSD, using criteria based on grains orientation spread (GOS) and grain tolerance angle, and further correlated with the mechanical properties. The strong recrystallization texture (Goss texture ({110} <001>), and rotated Goss texture ({110} <110>)) were observed in CT-MAF sample as compared to RT-MAF sample. The average ultimate tensile strength and average hardness increased after the CT-MAF to 370 MPa and 124 VHN, respectively, almost average ultimate tensile strength (UTS) increased by 23% and average hardness increased by 33% as compared to RT-MAF sample. It was observed that at −147 °C processing temperature strain hardening mechanism was dominated in CT-MAF sample, whereas due to the room temperature processing temperature softening mechanism was dominated in RT-MAF sample. © 2022 Elsevier Ltd